Development of hybrid algorithm of residual bootstrap artificial neural network based on sukuk volatility forecast model. - Nurul Hila Zainuddin (Tanjong Malim, 2018)
Development of hybrid algorithm of residual bootstrap artificial neural network based on sukuk volatility forecast model. by Nurul Hila Zainuddin